HUBUNGAN HUKUM PENGELOLAAN WAKAF ANTARA NAZHIR DAN BADAN WAKAF INDONESIA PROVINSI SUMATERA UTARA TERHADAP TANAH WAKAF YANG BELUM TERDAFTAR (Studi di Kota Medan) - Syaddan Dintara Lubis; Muhammad Yamin Lubis; Utary Maharany Barus; Rosnidar Sembiring (Universitas Sumatera Utara, 2015)
ABSTRAK Of 1,242 parcels of wakaf land in Medan, 663 of them have been certified and 393 have not, and 186 of them were in the process in the National Land Board and several of them have not been registered which will possibly cause dispute. Wakaf is expected to be able to improve people’s welfare, especially Moslems. Therefore, it is necessary to keep the assets of registered and unregistered wakaf land. The problems of the research were as follows: first, how about the correlation between Nazir and BWI (Indonesian Wakaf Board) of North Sumatera, related to the management of unregistered wakaf land in Medan; secondly, how about the obstacles faced by Nazir and BWI of North Sumatera in managing unregistered wakaf land; and thirdly, how about the role BWI in controlling the management of unregistered wakaf land in Medan. Keywords: Nazir, Indonesian Wakaf Board, Management of Wakaf Land